Multispecies Ethnography: Life Writing of Marine Animals in Cuthbert Collingwood - Lu, Li-Ru (SARE: Southeast Asian Review of English, 2023)
Prior to the mid-nineteenth century, Formosa (now Taiwan) was little known to European and American travelers. To explore this terra incognita, plenty of Western explorers, navy investigators, merchants, and naturalist scientists visited Formosa after the opening of Ta-kau Port and Keelung Port for trade in 1860. These travellers made observations and documented the unknown landscapes and species in Formosa and its neighbouring islands. Mostly written in the form of travel journals and natural histories, the works of these Western visitors are pioneering multispecies ethnographies that delineate nineteenth-century Formosa’s flora, birds, land animals and marine animals. This essay focuses on the life accounts and natural histories of an English traveller in this period — Cuthbert Collingwood (1826-1908). It explores the ways Collingwood’s Rambles of a Naturalist on the Shores and Waters of the China Sea represents Formosan marine animals and their habitats. It addresses the following questions: How did Collingwood introduce his readers to understanding marine animals in mid-nineteenth-century Formosa and how did he report his scientific observations on the lives of Formosa’s oceanic species? Did Collingwood evince his appreciation for marine species or express an environmentalist tone? How might Collingwood’s delineation of Formosa’s marine animals reveal an environmental consciousness and proto-ecological sensibilities?